Physical layer security of MIMO wireless systems with adaptive modulation - Hui LI; Guangqiu LI; Yancui LUO; Huizhi LIU (Dianxin kexue)
To solve the problems of low spectral efficiency and poor performance of physical layer security (PLS) in single-input single-output (SISO) wireless systems with adaptive modulation in the presence of an active eavesdropper, multiple-input multiple-output (MIMO) wireless systems with secure adaptive modulation (SAM) were proposed.The design idea was to improve the spectral efficiency of the main channel by antenna diversity technology, which used the transmit antenna selection (TAS) at the transmitter and the maximal ratio combining (MRC) at the legitimate receiver to improve the signal-to-noise ratio.Simultaneously, the PLS of the legitimate receiver was guaranteed by limiting the bit error rate of the active eavesdropper so that it could not demodulate the confidential information from the main channel.With the joint constraints of the average transmission power and PLS, the optimal switching thresholds and the analytical expressions of spectral efficiency and the eavesdropper’s average bit error rate of the SAM-MIMO systems were derived.Numerical and simulation results show that SAM systems using TAS/MRC technology can not only improve the spectral efficiency of the main channel, but also ensure the PLS against the active eavesdropper, compared with the SAM-SISO systems.